V.2 - Basu, Kaushik (ed.); Kanbur, Ravi (ed.) (New Delhi, 2009)
Amartya Sen has made deep and lasting contributions to the academic disciplines of economics, philosophy, and the social sciences more broadly. He has engaged in policy dialogue and public debate, advancing the cause of a human development focused policy agenda, and a tolerant and democratic polity. This argumentative Indian has made the case for the poorest of the poor, and for plurality in cultural perspective. It is not surprising that he has won the highest awards, ranging from the Nobel Prize in Economics to the Bharat Ratna, India's highest civilian honor. This public recognition has gone hand in hand with the affection and admiration that Amartya's friends and students hold for him.
Volume 2. Society, Institutions, and development.
Keywords: Welfare economics